Effects of xanthan gum on atomization and deposition characteristics in water and Silwet 408 aqueous solution - Wang, Shilin; He, Xiongkui; Song, Jianli; Wang, Shuangshuang; Jia, Xiaoming; Ling, Yun (International Journal of Agricultural and Biological Engineering, 2018)
In order to investigate the effects of viscosity on spray formation and utilization of pesticide, different concentrations of xanthan gum (XG) were added into water and 0.1% Silwet 408 aqueous solution. Droplet size, relative span (RS), fan angle, length of breakup and maximum retention (Rm) were measured with the LU120-02 nozzle spraying under the pressure of 0.3 MPa. The dynamic spreading of the different solutions on maize leaves was tested using a 5 μL micro-injector. The results showed: VMD, RS, length of breakup and Rm went up as the increasing of XG concentration in the range of 0-0.5% with the same solution, while the fan angle of nozzle and spreading area on maize leaf showed the opposite tendency. Silwet 408 could reduce the surface tension of liquid, which could alter the dominant mode of spray formation and lead to earlier sheet breakup, especially in low viscosity solutions. Under the same concentration of XG the addition of Silwet 408 could reduce the RS of drop size spectrum but has no effect on VMD or fan angle. In water solution, there was no difference with different concentrations of XG in the spreading time on maize leaf. Besides, in the 0.1% Silwet 408 aqueous solution, the spraying time and area were several-fold of that in water with same XG concentration. Moreover, with the same XG concentration, the smaller surface tension liquid indicated lower Rm, and the difference was magnified as the concentration increases. This work has demonstrated that initial spray characteristics such as droplet size and RS, fan angle, length of breakup, Rm and spreading area can vary depending on the viscosity of spray liquids. Therefore, by transforming the viscosity of the spray liquid to adjust the droplet spectrum to reduce drift, increasing the Rm and spreading area to improve liquid utilization and reduce the usage of pesticides.Keywords: atomization, xanthan gum, spray, droplet size, breakup length, dynamic spreadingDOI: 10.25165/j.ijabe.20181103.3802Citation: Wang S L, He X K, Song J L, Wang S S, Jia X M, Ling Y. Effects of xanthan gum on atomization and deposition characteristics in water and Silwet 408 aqueous solution. Int J Agric & Biol Eng, 2018; 11(3): 29–34.